2017
DOI: 10.3390/ijms18112356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intranasally Delivered rh-VEGF165 on Angiogenesis Following Cerebral Hypoxia-Ischemia in the Cerebral Cortex of Newborn Piglets

Abstract: Background: Vascular endothelial growth factor (VEGF) stimulates vascular genesis and angiogenesis. Cerebral Hypoxia-Ischemia (HI) leads to the reduction of vasculature in the cerebral cortex of newborn piglets. Objective: The present study tests the hypothesis that post-hypoxia intranasal administration of recombinant human VEGF165 (rh-VEGF165) for 3 days increases the vascular density in the cerebral cortex of newborn piglets without promoting neovascularization. Design/Methods: Ventilated newborn piglets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Some studies confirmed that the lesions continue to expand during the early stages of HIBD 22,23 , a result consistent with the results of this experiment; thus, internal structural changes of such lesions should be accurately assessed. Due to the strong homology between pig www.nature.com/scientificreports/ and human brain tissues 24 , newborn piglets were selected as the subjects of this experiment, and the HIBD model was successfully established in piglets in the previous experiment, and corresponding results were obtained 22 . Currently, kurtosis parameters are considered more sensitive than diffusion parameters for the evaluation of ischemic lesions by DKI 18,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies confirmed that the lesions continue to expand during the early stages of HIBD 22,23 , a result consistent with the results of this experiment; thus, internal structural changes of such lesions should be accurately assessed. Due to the strong homology between pig www.nature.com/scientificreports/ and human brain tissues 24 , newborn piglets were selected as the subjects of this experiment, and the HIBD model was successfully established in piglets in the previous experiment, and corresponding results were obtained 22 . Currently, kurtosis parameters are considered more sensitive than diffusion parameters for the evaluation of ischemic lesions by DKI 18,25 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, to further dissect out the specific contribution of HIF1α in neuronal cell death/survival, we used pharmacological strategies with a known HIF1α inhibitor 2-methoxyestradiol (2ME2), or a PHD inhibitor dimethyloxalylglycine (DMOG) that stabilizes HIF1α, to manipulate HIF1α levels in immature primary cortical neurons. We investigated whether acute manipulation of HIF1α expression has any impact on neuronal viability, as well as its effects on the HIF1α substrates, vascular endothelial growth factor (VEGF) and erythropoietin (Epo), both of which are proven to be beneficial in brain repair in rodent models of neonatal HI and neonatal stroke [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The most well-recognized mechanisms of NBP activity are improving the microcirculation, promoting angiogenesis and increasing cerebral blood flow in the ischemic area. Ki-67 is a nuclear protein involved in cell proliferation, and has been used as a marker of vessel density [ 26 ]. We found that NBP treatment increased Ki-67 levels in the ischemic area in our pMCAO model, illustrating that NBP can improve angiogenesis in the ischemic region.…”
Section: Discussionmentioning
confidence: 99%